Catalytic iron in acute myocardial infarction complicated by cardiogenic shock — A biomarker substudy of the IABP-SHOCK II-trial. (15th January 2017) - Fuernau, Georg; Traeder, Florian; Lele, Suhas S.; Rajapurkar, Mohan M.; Mukhopadhyay, Banibrata; de Waha, Suzanne; Desch, Steffen; Eitel, Ingo; Schuler, Gerhard; Adams, Volker; Thiele, Holger
Abstract: Background: Catalytic iron (CI) is unbound ferric iron with the potential to generate reactive oxygen species with further deleterious vascular effects. In acute coronary syndromes, high levels of CI are linked to all-cause mortality. The prognostic impact of CI and iron metabolism in cardiogenic shock (CS) is currently undetermined. Aims of this study were to investigate the prognostic impact of CI and to identify predictors of high CI levels in patients with CS complicating acute myocardial infarction. Methods: The Intraaortic Balloon Pump in Cardiogenic Shock II (IABP-SHOCK II) trial randomized 600 patients with CS to either therapy with intraaortic balloon pump or control. In 185 of these patients, blood samples were systematically collected at baseline and day 3. CI levels were measured using a modified bleomycin detectable iron assay. Furthermore, levels of free hemoglobin, total serum iron, transferrin, total iron binding capacity, ferritin, hepcidin, and transferrin saturation were assessed. Results: Patients with baseline CI levels in the highest quartile had a worse outcome in comparison to patients with lower CI (day 1: HR 1.91 [1.11–3.31], p = 0.005; day 3: HR 2.15 [1.06–4.34], p = 0.01). In multivariable Cox-regression analysis baseline CI remained an independent predictor of 30-day mortality (HR per 10LOG 2.08 [1.25–3.47], p = 0.005). Predictors of CI levels on day 3 were baseline CI, bleeding events, and baseline troponin T. Conclusions: CI levels were associated with increased short-term mortality in CS complicating acute myocardial infarction. High levels of CI at day 3 were associated with bleeding and high troponin levels.